Transient Response and Ionic Dynamics in Organic Electrochemical Transistors - Zhao, Chao; Yang, Jintao; Ma, Wei (Nano-Micro Letters, 2024)
The rapid development of organic electrochemical transistors (OECTs) has ushered in a new era in organic electronics, distinguishing itself through its application in a variety of domains, from high-speed logic circuits to sensitive biosensors, and neuromorphic devices like artificial synapses and organic electrochemical random-access memories. Despite recent strides in enhancing OECT performance, driven by the demand for superior transient response capabilities, a comprehensive understanding of the complex interplay between charge and ion transport, alongside electron–ion interactions, as well as the optimization strategies, remains elusive. This review aims to bridge this gap by providing a systematic overview on the fundamental working principles of OECT transient responses, emphasizing advancements in device physics and optimization approaches. We review the critical aspect of transient ion dynamics in both volatile and non-volatile applications, as well as the impact of materials, morphology, device structure strategies on optimizing transient responses. This paper not only offers a detailed overview of the current state of the art, but also identifies promising avenues for future research, aiming to drive future performance advancements in diversified applications. Highlights: 1 Transient response plays a crucial role as a performance indicator for organic electrochemical transistors (OECTs), particularly in their application in high-speed logic circuits and neuromorphic computing systems. 2 This review presents a systematic overview on the fundamental principles underlying OECT transient responses, emphasizing the essential roles of transient electron and ion dynamics, as well as structural evolution, in both volatile and non-volatile behaviors. 3 We also discuss the materials, morphology, device structure strategies on optimizing transient responses.